Modern Muslim Theology - Faraz Sheikh (American Journal of Islam and Society, 2019)
True to its title, this book engages God and the world with faith and imagination. It is a work inspired by faith and that aims to inspire faith, a work of Muslim theology that does the work of theology, a term which for Nguyen “names a life-encompassing and faith-affirming process with which every person is already engaged”.